PHENOTYPIC ASSESSMENT OF F1 WILD Clarias gariepinus, Heterobranchus bidorsalis AND HYBRID TO REDUCE INBREEDING IN NIGERIA - BADMOS, L. A; AKINTOLA, S. L.; ANETEKHAI, M. A.; ELEGBEDE, I. O. (Nigerian Journal of Fisheries, 2025)
Clarias gariepinus and Heterobranchus species dominate Nigeria’s aquaculture sector but face declining production due to inbreeding caused by poor broodstock management and undocumented breeding practices. This study assessed the first f ilial generation of wild strains (wild population) and their hybrids from River Benue, River Ogun, Lake Chad, and a Lagos cultured population (exis ng farmed Clarias gariepinus popula on collected from LASU fish farm) to help mitigate inbreeding and support sustainable catfish farming in Nigeria. Sampling covered three major geographic zones and a sample of an exis ng farmed C. gariepinus popula on, used as a control. A total of 300 catfish samples were analyzed for length–weight relationship, condition factor K, and 19 morphometric plus six meristic traits. Data were standardized and analyzed using analysis of variance (ANOVA) and Principal Component Analysis (PCA) to determine significant morphological differences among wild and cultured strains. The results showed that length–weight relationships and condition factors varied, with the MALIJB (Intraspecific hybrid of the cross between MAL male and IJB female), recording the highest growth coefficient (b = 3.818, r² = 0.922) and condition factor (K = 1.233) compared to pure strains like MAK (Wild popula on of Heterobranchus bidorsalis from River Benue; Benue strain) (b = 2.164) and LAG (exis ng farmed Clarias gariepinus popula on collected from LASU fish farm) (b = 2.019). Morphometric and meristic traits differed significantly, with the IJB (Wild strain of Clarias gariepinus from Ogun River; Ogun strain) showing the highest standard length (38.95 cm). PCA revealed that six principal components explained 84.86% of total variation, highlighting traits such as anal length, eye diameter, and post-orbital length. The IJB and the hybrids involving IJB, especially when IJB was used as the female parent, indicating its strong potential as a candidate strain for improved aquaculture performance.